Children’s participation in custody dispute involving interfaith parents - Zakaria M.Z.; Yaakob A.; Ahmad A.; Musa A.S.; Rajuddin A.S.; Awal N.A.M.; Samuri M.A.A.; Mushaddad Hasbullah (American Scientific Publishers, 2024)
Indexed by SCOPUS